Predicting health-related quality of life in women with infertility based on alexithymia, sexual satisfaction due to the mediating role of perceived infertility stigma - amini masouleh, Masumeh; namvar, Hooman; Agha Yousefi, Alireza (Researcher Bulletin of Medical Sciences, 2022)
The present study predicts health-related quality of life in women with infertility based on alexithymia, sexual satisfaction with respect to the mediating role of perceived infertility stigma. The method of this research was descriptive (non-experimental) and the research design was a correlation of structural equations. The statistical population of the present study was infertile women in Tehran in 1399. The sample size was 250 and according to the formula for determining the sample size (1992). The research instruments included standard questionnaires such as Weber (1992), Bagby, Parker & Tyler (1994), Larson (1988) and Perceived Stigma of Infertility (2014). Data analysis was performed using SmartPLS software. The results showed that perceived stigma of infertility had a mediating role in the relationship between mood variables and sexual satisfaction with health-related quality of life in women with infertility.